A participação do vendedor no processo de cocriação de produtos: um estudo na indústria têxtil . - Casagrande Junior, Guilherme Cirello (Universidade do Vale do Rio dos Sinos, 2018)
The way companies work and interact with the market has changed over the last years. The constant preoccupation with profits has lost strength and has made room for the context of generation of value, supported by the Service Dominant Logic (SDL). Within the SDL, among various premises, the one that deals with the cocreation of value stands out, occurring as a result of the processes that take place among stakeholders, in the interest of valuing a business and making it more competitive. This research addresses the seller as a stakeholder and cocreator of value. In addition, the study investigates the antecedents and the consequents of cocreation. For that purpose, a theoretical model was developed, contemplating the constructs of Open Communication, Learning Orientation, Ability of Cocreating, Intention to cocreate, Cocreation, Creation of Relational Value, Perfomace in Sales, and New Products Creation. Hence, a survey was conducted with 415 sellers acting in the B2B market in the textile industry. An analysis of this data was made based on multivariate statistics, making use of Structural Equation Modeling in order to test the model and investigate the relation between the constructs that integrate this study. Findings support the constructs of Open Communication, Learning Orientation, Ability, and Intention as antecedents of Cocreation. As soon as it is applied, cocreation assume a mediation role, and generates more relational value, improve the performance in sales, and the new products creation, since the knowledge acquired by a seller through their experience of selling is fully utilized. In addition, it is made possible for one to create, change and contribute with solutions and added value to the market.
Keywords: Cocriação; Vendedor; Antecedentes; Consequentes; Criação de novos produtos; Cocreation; Seller; Antecedents; Consequents; New product creation; ACCNPQ::Ciências Sociais Aplicadas::Administração